Accumulation of heavy metals in leaves of tree species on the ash and slag dumps of the Burshtyn Thermal Power Plant - Semak, Uliana; Myroslava, Mylenka (ScienceRise: Biological Science, 2023)
Thermal power plant (TPP) facilities are considered as one of the major reasons for environmental pollution. Ash and slag dumps as a special construction for storage of combustion wastes of TPPs are recognized as sources of heavy metals (HMs) contamination for surrounding ecosystems. The present study is the first report of analyzing HMs contamination of the ash and slag dumps of the Burshtyn TPP. The aim of the study is to estimate the content of HMs in the technogenic substrates of ash and slag dumps and investigate soil-plant interactions through analyzing potential of HMs accumulation in the leaves of native dominant woody species. Materials and methods of research. Soil sampling was carried out in the period of July 2021 at previously determined points. The most common woody species (Populus tremula L., Betula pendula Roth., Salix caprea L.) were selected for testing of HMs accumulation abilities. Samples of plants and soil were subjected to an atomic absorption spectrometer for being analyzed for heavy metals: Cd, Zn, Ni, Cu, Pb, Mn and Fe. Results of research and discussion. The results showed that the substrates of ash and slag dumps of the Burshtyn TPP were mainly contaminated by lead, copper and cadmium. All tested species concentrated high amounts of magnesium, iron, zinc and low concentration of cadmium. Bioaccumulation factor reflected the highest abilities of accumulation of zinc in all tested species and low level of bioaccumulation of cadmium. The highest index of biochemical activity showed Betula pendula. Salix caprea were found as a promising species for remediation due to intensive accumulation of such elements like cadmium, lead, copper, zinc and nickel. Conclusions and prospects for further research. We consider plant organisms particularly useful for analyzing HMs accumulation as they can provide a cost-effective and long-term approach for bioindication and monitoring HMs pollution. Moreover, vegetation covers could be used for remediation of HMs contaminated sites